E-183 Proximal anchoring technique for flow diverters in the mobile cervical segment: experience in 9 petrocervical flow diversion cases. (23rd July 2022) - Campos, J; Zarrin, D; Meyer, B; Golshani, K; Beaty, N; Bender, M; Colby, G; Lin, L; Coon, A
Abstract : Background: Flow diverting stents (FDS) are routinely used to safely reconstruct the arteries of the head and neck. When these constructs in the internal carotid artery (ICA) extend proximally into the mobile cervical segment the FDS runs the risk of migration or proximal intimal hyperplasia reaction from normal movement of the neck post-procedure. We report our experience using a novel proximal anchoring technique to prevent this potentially deleterious result. Methods: We retrospectively reviewed a prospectively-maintained IRB-approved institutional database of the senior authors to identify cases where patients undergoing flow diversion stent (FDS) treatment in the mobile petrocervical segments had the proximal FDS 'anchored' down with a laser-cut nitinol stent. Case details were recorded including patient demographics, pathology, devices used, and technical success. Results: FDS treatment was successfully performed in the mobile cervical segment a total of 9 times over the study period (December 2019 to January 2022). Each case involved a complex ICA dissection with 66% (n=6) having an accompanying pseudoaneurysm. Fifty-six percent (n=5) were female. Surpass Streamline was the FDS utilized in all cases. An average of 2 +/- 1 FDS devices were utilized (range 2–4 FDS), with each case utilizing a laser-cut nitinol carotid stent as proximal anchor stent. Each case received 1 proximal anchor stent with average stent diameter of 7 +/- 1 mm (range 6–8 mm) and length of 42 +/- 12 mm (range 30–60mm). No cases of stent migration or proximal neointimal hyperplasia were seen on most recent control angiography. Conclusion: Utilization of the proximal anchoring technique on FDS constructs in the mobile cervical ICA segment may provide additional protection from stent migration and intimal reaction attributed to patient neck movement post-procedure. Disclosures: J. Campos: None. D. Zarrin: None. B. Meyer: None. K. Golshani: None. N. Beaty: 2; C; Proctor for Medtronic Neurovascular, Stryker Neurovascular, CMO of NeuroMedica. M. Bender: None. G. Colby: 2; C; Consultant for Medtronic Neurovascular, MicroVention-Terumo, Stryker Neurovascular. L. Lin: 2; C; Consultant/Proctor: Medtronic Neurovascular, Stryker Neurovascular, MicroVention-Terumo, Rapid Medical, Bolt. A. Coon: 2; C; Consultant/Proctor: Avail MedSystems, Imperative Care, InNeuroCo, Medtronic Neurovascular, MicroVention-Terumo, Q'apel, Rapid Medical, Stryker Neurovascular, Sequent Medical.